2003
DOI: 10.1037/0022-006x.71.3.443
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of violence and self-harm in mentally disordered offenders: A prospective study of the efficacy of HCR-20, PCL-R, and psychiatric symptomatology.

Abstract: The efficacy of the Historical, Clinical, and Risk Management Scales (HCR-20; C. D. Webster, D. Eaves, K. S. Douglas, & A. Wintrup, 1995), Psychopathy Checklist-Revised (PCL-R; R. D. Hare, 1991), Beck Hopelessness Scale (BHS; A. T. Beck, A. Weissman, D. Lester, & L. Trexler, 1974), and Brief Psychiatric Rating Scale (BPRS) to predict violence and self-harm in 34 institutionalized mentally disordered offenders was assessed. Both the HCR-20 and BPRS were strong predictors of violence whereas the PCL-R had modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
129
5
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(162 citation statements)
references
References 37 publications
17
129
5
7
Order By: Relevance
“…This is consistent with previous studies in which Factor 2 (containing criminal and impulsivity variables) has been found to be superior to Factor 1 (consisting primarily of personality variables) in predicting future criminal behaviour (Belfrage, Fransson, & Strand, 2000;Gray et al, 2003;de Vogel, de Ruiter, Hildebrand, Brechje, & van de Ven, 2004). The investigation of psychopathy in men and women in our study revealed important commonalities and differences.…”
Section: Resultssupporting
confidence: 92%
“…This is consistent with previous studies in which Factor 2 (containing criminal and impulsivity variables) has been found to be superior to Factor 1 (consisting primarily of personality variables) in predicting future criminal behaviour (Belfrage, Fransson, & Strand, 2000;Gray et al, 2003;de Vogel, de Ruiter, Hildebrand, Brechje, & van de Ven, 2004). The investigation of psychopathy in men and women in our study revealed important commonalities and differences.…”
Section: Resultssupporting
confidence: 92%
“…This analysis did not address the influence of early maltreatment on the risk of self-harm in individuals with psychosis, given that different factors may influence this relationship (see e.g. Gray et al, 2003).…”
Section: Limitationsmentioning
confidence: 99%
“…Some instruments, however, have been explicitly designed for, or validated within, specific offender populations. [47][48][49] The first stage of the project involved a scoping exercise to systematically identify available instruments that could be used to screen for self-harm. A search was carried out with the Scopus database [encompassing MEDLINE, PsycINFO, Cumulative Index to Nursing and Allied Health Literature (CINAHL) and EMBASE], using appropriate search terms such as 'self-harm', 'self-injury', 'suicide ideation', 'prison', 'jail', 'risk', 'questionnaire' and 'screen'.…”
Section: Scoping Methodsmentioning
confidence: 99%
“…Limited evidence suggests that the Beck Hopelessness Scale (BHS) 46 was predictive of self-harm among offenders with mental disorders. 47 Several other scales are available for assessing the risk of self-harm, for example the Self-Harm Inventory (SHI), 48 but few have been validated for routine use in offender populations. A newer scale, Suicide Concerns for Offenders in Prison Environment (SCOPE), 49 has been specifically developed to assess vulnerability to risk of suicide and non-fatal self-harm behaviour in young adult offenders but, again, has not been tested with regard to routine implementation in prisons, for those of older ages or for prospective predictive validity.…”
Section: Implications For the Prison Systemmentioning
confidence: 99%